2021
DOI: 10.1089/tmj.2020.0295
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Telemedicine Perceptions During the COVID-19 Pandemic

Abstract: Background: Telemedicine utilization increased exponentially due to the coronavirus disease 2019 (COVID-19) pandemic. As a result, most clinicians now have experience with telemedicine. Questions/Purposes: We studied factors independently associated with a clinician desiring to continue telemedicine services after the COVID-19 pandemic. Secondarily, we sought factors independently associated with clinician satisfaction with the quality of care provided through telemedicine and factors associated with telemedic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 24 publications
2
67
0
Order By: Relevance
“…36 A study of primarily medical specialties found high likelihood to continue telemedicine but lower satisfaction with telephone visits than video. 37 These prior surveys have not highlighted the safety net, nor safety net-specific patient barriers. The telemedicine explosion of rapid implementation, without dedicated resources or standard work, is common to many safety-net settings that disproportionately care for low-income populations.…”
Section: Discussionmentioning
confidence: 99%
“…36 A study of primarily medical specialties found high likelihood to continue telemedicine but lower satisfaction with telephone visits than video. 37 These prior surveys have not highlighted the safety net, nor safety net-specific patient barriers. The telemedicine explosion of rapid implementation, without dedicated resources or standard work, is common to many safety-net settings that disproportionately care for low-income populations.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the above, only a few studies have been focused on measuring the perception and acceptance of healthcare providers toward robotic tools in the COVID-19 pandemic (Betriana et al, 2020 ; Miner et al, 2020 ; Viswanathan et al, 2020 ). Several studies analyzing the acceptability and adherence of technology in healthcare, such as home healthcare robots and information systems, have shown that more than 40% of these technologies have failed or have been abandoned in the last two decades (Alaiad and Zhou, 2014 ; Greenhalgh et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, many surveyed physicians have reported that the lifted telehealth restrictions have eased their workload more efficiently, leading to increased care quality and greater satisfaction with newly adopted technology. 24 Ultimately, these policies support the promise of telehealth with its proven effectiveness to connect more patients with the quality care they deserve and open the door to have telehealth and make its place in the future of healthcare.…”
Section: Introductionmentioning
confidence: 99%